Production of Poly-α-hydroxybutyrate (PHB) from Sago Starch by The Native Isolate Bacillus megaterium PSA10 - Nur Arfa Yanti; Langkah Sembiring; Sebastian Margino (Indonesian Journal of Biotechnology, 2006)
A new bacterial strain that produces amylase and poly-α-hidroxybutyrate (PHB) using sago starch as carbon source was characterized and identified to be member of the Bacillus megaterium group based on phenotypic characteristics and 16S rDNA gene sequences. Amylase activity was determined spectrophotometrically on the basis of substrate concentration reduction. PHB production was quantified with UV spectrophotometer. The polymer produced by B. megaterium PSA10 was identified by Fourier Transform Infrared spectroscopy (FTIR). The result of the study showed that the amylase specific activity B. megaterium PSA10 was 593,61 DUN/mg protein and PHB production from sago starch was 52,28 % of cell dry weight (CDW). FTIR analysis of the polymer indicated that the strain B.megaterium PSA10 was a potent PHB producer.